2002
DOI: 10.1055/s-2002-36394
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Second-Generation Antipsychotics and the Evolving Standard of Care in Italy

Abstract: The present study was carried out to investigate the routine use of second-generation antipsychotic drugs in the Italian psychiatric care system. Seven outpatient psychiatric services enrolled a consecutive case series of patients who were being treated, or had started treatment, with clozapine, olanzapine, risperidone, or quetiapine. Information on sociodemographic and clinical variables, current psychotropic drug use, side-effects and past use of typical drugs was collected. In addition, patient symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2003
2003
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
0
18
0
4
Order By: Relevance
“…The literature suggests that clinicians often use secondgeneration agents for indications not approved by the Food and Drug Administration (13)(14)(15)(16). For example, a study in veterans found that although a majority (57%) of patients (n = 73,981) were prescribed antipsychotic drugs for schizophrenia in a 4-month period, nearly 43% had diagnoses other than schizophrenia (13).…”
Section: Off-lmhel Use Of Antipsychotic Drugsmentioning
confidence: 99%
“…The literature suggests that clinicians often use secondgeneration agents for indications not approved by the Food and Drug Administration (13)(14)(15)(16). For example, a study in veterans found that although a majority (57%) of patients (n = 73,981) were prescribed antipsychotic drugs for schizophrenia in a 4-month period, nearly 43% had diagnoses other than schizophrenia (13).…”
Section: Off-lmhel Use Of Antipsychotic Drugsmentioning
confidence: 99%
“…studies have been done in Germany [1, 2, 9, 10, 18, 20, 21, 25, 29 -32, 35] . Therefore, the aim of this retrospective study was to determine (1) how common off-label use is in one German psychiatric hospital, (2) whether there has been a difference in the frequency of off-label prescribing since the FSC decision, and (3) how off-label use varies by patient characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective evaluation of prescribing involving 209 outpatients in Italy found that over half of them were given offlabel prescriptions of atypical antipsychotics (Barbui et al, 2002). A similar situation was found in a prescription review of 173 patients attending pharmacies in Austria, which revealed that twothirds of them were receiving antipsychotics for unlicensed indications (Weiss et al, 2000).…”
Section: General Adult Psychiatrymentioning
confidence: 60%